1995
DOI: 10.1111/j.1600-0447.1995.tb09546.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of post‐stroke depression in a rehabilitative center

Abstract: This was a prospective study of 52 stroke patients. The incidence of post-stroke depression was 55%. A past history of depression was significantly associated with the clinical assessment of depression. There was no association between the clinical assessment of depression and type and site of lesion and intellectual impairment. The clinical assessment of depression was significantly associated with the degree of functional impairment. The clinical assessment of depression also correlated well with Hamilton De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
1
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 16 publications
8
42
1
7
Order By: Relevance
“…A past history of depression has been shown previously to be a risk factor for post-stroke depression (Andersen et al, 1995). The current study found that a past history of depression, anxiety, or "nerves" conferred at least an eight-fold risk of post-stroke depression, consistent with other research (Ng et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A past history of depression has been shown previously to be a risk factor for post-stroke depression (Andersen et al, 1995). The current study found that a past history of depression, anxiety, or "nerves" conferred at least an eight-fold risk of post-stroke depression, consistent with other research (Ng et al, 1995).…”
Section: Discussionsupporting
confidence: 89%
“…Staff should determine whether stroke patients have a past psychiatric history. The literature suggests that questioning either the patient or a family member provides sufficient detail for the purpose of screening (Eastwood et al, 1989;Ng et al, 1995). Thirdly, the current study supports previous work identifying neuroticism as a risk factor for post-stroke depression.…”
Section: Discussionsupporting
confidence: 84%
“…No primeiro mês pós-AVC, em pacientes admitidos em um centro de reabilitação, o prejuízo funcional foi responsável por 48% da variância na avaliação da depressão leve e moderada segundo o estudo de Ng et al 14 . A cada unidade reduzida na escala de Barthel aumentava-se em 80% a probabilidade do paciente estar deprimido.…”
Section: Prejuízo Funcionalunclassified
“…Pacientes com história de depressão apresentaram um risco 2,3 vezes maior de desenvolverem depressão pós-AVC e quase três vezes mais de apresentarem depressão maior 18 . No estudo Ng et al 14 , a história pregressa de depressão estava fortemente associada à depressão pós-AVC e foi o fator responsável por 64% da variância na avaliação do diagnóstico da depressão leve e moderada. Todos os episódios pregressos de depressão, apresentados pelos pacientes estudados, foram caracterizados como reativos pelos autores e haviam remitido, espontaneamente, sem tratamento.…”
Section: História De Depressãounclassified
See 1 more Smart Citation